FAKTOR-FAKTOR YANG MEMENGARUHI PENGGUNAAN PEMBAYARAN ELEKTRONIK NON-BANK - Nina Karina Karim; Siti Atikah; Indria Puspitasari Lenap (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2022)
Transformation of payment systems triggered by advances in information technology and development of electronic gadgets have provided easier ways to conduct payments, starting from sales transaction to bill settlements. This research aims to seek what factors determine the choice to use non-bank electronic payment system and its impact on personal accountability and financial planning. User opinion on factors that comes into consideration in selecting non-bank electronic payment system is gathered through questions based on the criteria set by Theory of Planned Behavior. From 316 questionaires submitted by GoogleForm, it can be concluded that the three main factors that are considered in using non-bank electronic payment system are ease of payment process, transaction speed, and personal data security. Accuracy and accountability reflected from the availability of transaction history within the payment application only ranked fifth in the factors that influence the decision to select and use non-bank electronic payment system.